The Improvement of Scientific Attitudes through Problem-based Learning with Differentiated Instruction in Physics Subject - Windarto, Yusfrina Yanuarti; Pranata, Pranata; O, Okimustava (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2023)
This study aims to improve the scientific attitude of XG students at SMA N 1 Purworejo through the application of the Problem-Based Learning (PBL) model with a differentiation approach in physics education. This research is a classroom action research conducted over two cycles. Data were collected through observations using an observation sheet. The results from Cycle I showed an average class score of 71% out of 100%, with three out of nine indicators rated as "poor." In Cycle II, the average class score improved to 85% out of 100%, with seven indicators rated as "very good" and two indicators rated as "good." Based on data analysis and discussion, there was an improvement in students' scientific attitudes through the implementation of the Problem-Based Learning model with a differentiation approach in physics education.